2018
DOI: 10.1155/2018/4049136
|View full text |Cite
|
Sign up to set email alerts
|

Resectional One Anastomosis Gastric Bypass/Mini Gastric Bypass as a Novel Option for Revision of Restrictive Procedures: Preliminary Results

Abstract: Background Revisional surgery is becoming a common and challenging practice in bariatric centers. The aim of this study was to evaluate resectional one anastomosis gastric bypass/mini gastric bypass (R-OAGB/MGB) as a revisional procedure. Methods From January 2016 to February 2017, data on 21 consecutive patients undergoing R-OAGB/MGB for weight loss failure after primary restrictive procedures were prospectively collected and analysed. Results Mean age was 39 ± 12 years (18–65), and 11 (52.3%) were women. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 37 publications
0
4
0
3
Order By: Relevance
“…3 Forest plot showing the effect of OAGB/MGB on BMI after 1-year follow-up [41]. This review of literature also showed that simultaneous gastric remnant resection, which was performed in some of the studies [21,23,25,26,29], has no significant effects on weight loss, but, in our opinion, it can only increase the risk for postoperative complications and hamper reversal surgery (Table 11).…”
Section: Publication Biasmentioning
confidence: 87%
“…3 Forest plot showing the effect of OAGB/MGB on BMI after 1-year follow-up [41]. This review of literature also showed that simultaneous gastric remnant resection, which was performed in some of the studies [21,23,25,26,29], has no significant effects on weight loss, but, in our opinion, it can only increase the risk for postoperative complications and hamper reversal surgery (Table 11).…”
Section: Publication Biasmentioning
confidence: 87%
“…Five patients (42%) underwent the revisional procedure due to weight regain, while seven patients (58%) underwent re‐OAGB for insufficient weight loss. After careful adhesiolysis of the anterior and posterior gastric wall, the gastric pouch was calibrated with a 40 French bougie and had a length extending to approximately 12 cm from the esophagogastric junction, 22 using purple or black Tri‐Staple EndoGIA™ 60 mm cartridges. The average length of the biliopancreatic limb created during re‐OAGB was 166 ± 31 cm.…”
Section: Resultsmentioning
confidence: 99%
“…Considerando lo anteriormente enunciado, existen estudios con seguimientos de 3 -5 años en donde se observan índices de conversión de GV hasta un 36% a 10 años. [1,3,7,10,[16][17][18]…”
Section: Respuesta Parcial O Inadecuada De La Gvunclassified
“…Se definió curación de DM como una HbA1c <6.5%, HbA1c <6% en combinación con glucometrías en ayuno <126 mg/dl, <110 mg/dl y/o <100 mg/dl sin tratamiento farmacológico para dichas patologías, en algunos estudios cumpliendo un periodo mínimo de 1 año. [2,4,11,16,17,27,33] Se observa que los pacientes que se les realizó un OAGB presentan índices mayores de curación en todas las patologías estudiadas. Un punto a considerar es el hecho que se tomó como base los pacientes que aun después de la GV persistian con su patología, por lo que el porcentaje total de pacientes que se logró remisión de DM, HTA y DL son mayores.…”
Section: Resolución De Comorbilidadesunclassified
See 1 more Smart Citation